A systematic modeling approach for layered soil considering horizontal and rotational foundation vibrations. (15th October 2020) - Shi, Jun-Yang
Highlights: A systematical approach is proposed to generate simplified models for layered soil. The proposed model considers the coupling between horizontal and rotational motion. The effectiveness of the proposed model is validated with theoretical solutions. The proposed model uses fewer parameters than an existing. Abstract: Several simplified models have been developed to simulate unbound soil for dynamic soil-structure interaction analysis in time domain. However, the existing models may have critical limitations for general applications. This study presents an approach to systematically generate lumped-parameter models with frequency-independent coefficients to represent the dynamic stiffness of rigid foundations in layered soil undergoing horizontal and rotational vibration. The components of the proposed model are determined from modularized units using a computational procedure, which simulates the coupling between the horizontal and rotational motion. This study applies the proposed model to simulate a non-uniform layered half-space and a uniform stratum on rigid rock. For surface and embedded foundations, the dynamic responses calculated by the proposed model agree well with theoretical solutions and computer program results. For embedded cylindrical foundations, the proposed model performs better and uses fewer parameters than an existing lumped-parameter model to simulate a soil layer on rock. Thus, the proposed systematic modeling approach shows a higher degree of adaptivity than traditional methods to generate simplified models for the simulation of layered soil considering coupled horizontal and rotational motion.